2017
DOI: 10.3174/ajnr.a5419
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sonographically Detectable Echogenic Foci in Pediatric Thyroid Carcinoma with Corresponding Histopathology: An Observational Study

Abstract: Sonographically detectable echogenic foci in malignant pediatric thyroid nodules can be reliably classified on the basis of American College of Radiology Thyroid Imaging, Reporting and Data System, with punctate echogenic foci composing the most common subtype. These echogenic foci do not represent psammomatous calcifications most of the time; instead, more than half of the malignant thyroid nodules with echogenic foci contained stromal calcifications or sticky colloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
10
4
Order By: Relevance
“…Intracystic CTA is strongly correlated with inspissated colloid content [ 16 ]. However, many cases of punctate NEF may correspond to dystrophic calcifications and colloid, as well as psammomatous calcifications [ 11 , 14 , 23 ] and it remains unclear whether the histopathologic feature of intrasolid punctate NEF with CTA is colloid or microcalcification [ 21 , 22 , 24 ]. Although the histopathologic features of large NEFs remain to be elucidated, they might have a relationship with those of intrasolid punctate NEFs without CTA based on the high rate of their concurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracystic CTA is strongly correlated with inspissated colloid content [ 16 ]. However, many cases of punctate NEF may correspond to dystrophic calcifications and colloid, as well as psammomatous calcifications [ 11 , 14 , 23 ] and it remains unclear whether the histopathologic feature of intrasolid punctate NEF with CTA is colloid or microcalcification [ 21 , 22 , 24 ]. Although the histopathologic features of large NEFs remain to be elucidated, they might have a relationship with those of intrasolid punctate NEFs without CTA based on the high rate of their concurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The US lexicon of microcalcifications primarily defines them as punctate (≤1 mm) echogenic foci with focal hyperechogenicity relative to the thyroid tissue within the solid component of a nodule [ 5 , 6 ]. Although the US feature of microcalcification is strongly associated with malignancy, some reports [ 7 , 11 ] have indicated that the term "microcalcification" is a misnomer because many punctate echogenic foci are found in benign nodules [ 12 ] and are not well correlated with psammomatous microcalcifications on histopathologic examinations [ 11 , 13 , 14 ]. Recent studies [ 12 , 15 ] have suggested that some types of NEF with a comet tail artifact (CTA) may be associated with malignancy, but this possibility remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, US features were compared with the findings at pathologic examination to investigate the US‐pathologic correlate of PEF. The Authors found that histopathological detected psammoma bodies were strongly correlated to the presence of PEF ( P < 0.001), data that disagree with previous studies 8,11 . In this view, the Authors argued for this discordance reflecting on their higher prevalence of psammoma bodies (74.6%) in the pathologically proven PTCs, compared to the rates previously reported (30.8%–40%) 8,11 .…”
mentioning
confidence: 70%
“…The Authors found that histopathological detected psammoma bodies were strongly correlated to the presence of PEF ( P < 0.001), data that disagree with previous studies 8,11 . In this view, the Authors argued for this discordance reflecting on their higher prevalence of psammoma bodies (74.6%) in the pathologically proven PTCs, compared to the rates previously reported (30.8%–40%) 8,11 . Among PTCs with PEF, 94.4% cases showed any type of calcified deposits or inspissated colloids.…”
mentioning
confidence: 72%
“…Based on the American College of Radiology (ACR) Thyroid Imaging Reporting and Data System (TI-RADS), 3 types of echogenic foci are potentially linked to malignancy [ 6 , 7 ]: macrocalcifications, punctate echogenic foci, and peripheral rim calcifications (or eggshell calcifications). Macrocalcifications have been reported to carry a mild risk of malignancy, while punctate echogenic foci, which are mostly accompanied by psammomatous calcifications in papillary thyroid cancer, have been regarded with a high possibility of malignancy [ 8 , 9 ]. Nevertheless, the literature on the malignancy probability of rim calcifications has remained controversial [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%